Floristic diversities and medicinal importance of selected sacred groves in Thrissur district, Kerala - Deepa MR; Sheema Dharmapal P and P. S. Udayan
Sacred groves are forest fragments of varying sizes, existing outside conventional forest areas in and around human inhabitation. It acts as safe sites for reproduction of variety of floral and faunal resources. An exploratory survey of different sacred groves of Thrissur District (10.52° N to 76.21° E), namely Adipparambukavu, Daivathinkavu, Kanisherykavu, Kottaichalippattukavu and Kottarathkavulead to the collection of 119 species coming under 104 genera and 51 families, representing 08 vulnerable, 12 endemic and 03 near threatened species. It includes 17.64% herbs, 19.33% shrubs, 41.18% trees and 21.85% climbers. Maximum diversity is present in Kanisherykavu (57 plant species and 36 families) and minimum diversity is present in Adipparambukavu (27 plant species belonging to 18 families). Fabaceae and Moraceae were the dominant families present in these sacred groves. Among these Kottarathkavu is well protected and is under the observation of Kerala Forest Department. It also harbours several valuable and medicinal plants beneficial for mankind. These groves serve as seed banks for future afforestation and can further help in education and research. Since sacred groves are gradually declining immediate attempts are needed to scientifically document and explore them to ensure their long term conservation.